2009
DOI: 10.1002/qua.21976
|View full text |Cite
|
Sign up to set email alerts
|

The importance of accurate interaction potentials in the melting of argon nanoclusters

Abstract: ABSTRACT:The melting temperatures of argon clusters Ar N (N = 13, 55, 147, 309, 561, and 923) and of bulk argon have been obtained from exchange Monte Carlo simulations and are compared using different two-body interaction potentials, namely the standard Lennard-Jones (LJ), Aziz and extended Lennard-Jones (ELJ) potentials. The latter potential has many advantages: while maintaining the computational efficiency of the commonly used LJ potential, it is as accurate as the Aziz potential but the computer time scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…We mention that we demonstrated recently that such an approach also leads to very accurate melting temperatures for neon and argon under normal conditions. 47,48 On the experimental side, the measurements presented by different research groups can deviate significantly ͑e.g., see the scatter of data in Fig. 3͒, and more accurate low-and high-pressure measurements for solid neon are required.…”
Section: Discussionmentioning
confidence: 99%
“…We mention that we demonstrated recently that such an approach also leads to very accurate melting temperatures for neon and argon under normal conditions. 47,48 On the experimental side, the measurements presented by different research groups can deviate significantly ͑e.g., see the scatter of data in Fig. 3͒, and more accurate low-and high-pressure measurements for solid neon are required.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,18 Although their presence has been known for a long time ͓e.g., the Axilrod-Teller term has been discussed in 1943 ͑Ref. 19͔͒, explicitly calculating them is computationally very demanding and has only become possible in the past few years.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,21 Recent work has investigated the effect of three-body interactions on melting points and specific heats for argon clusters. 4,5 It was found that the maximum of the heat capacity for Ar 147 shifts down from 50 to 46 K if three-body interactions are taken into account. This amounts to an effect of Ϸ10%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations